1988
DOI: 10.1093/carcin/9.11.2099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 7,12-dimethylbenz[a]anthracene metabolism and DNA binding in mammary epithelial cells from three rat strains with differing susceptibilities to mammary carcinogenesis

Abstract: The capacity of polycyclic aromatic hydrocarbons such as 7,12-dimethylbenz[a]anthracene (DMBA) to induce mammary carcinomas has been studied in three rat strains. Wistar/Furth (WF) rats are highly susceptible to DMBA-induced mammary carcinogenesis, Copenhagen (Cop) rats are completely resistant, and Fischer 344 (F344) rats have an intermediate susceptibility. We have previously shown that WF rats possess 'enhancer genes', which enhance susceptibility to induced mammary cancer. Cop rats, however, possess a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Of note, the F1 hybrid mice that were utilized involved the C57BL/6 genetic background, which has been shown to be resistant to transgene-induced mammary carcinogenesis [7;8] and the promotion of chemically-induced skin tumors [9]. In contrast, the Fischer rats that were used in this study have varying susceptibility to diverse tumors that is dependent upon both the inducing agent and tumor site [10][11][12][13]. Given the variations in tumor susceptibility observed among different strains of rodents, use of multiple strains of mice and rats may be more reflective of the genetic variability observed in humans.…”
Section: Assessment Of Bisphenol A-induced Carcinogenicity In Adult Rmentioning
confidence: 99%
“…Of note, the F1 hybrid mice that were utilized involved the C57BL/6 genetic background, which has been shown to be resistant to transgene-induced mammary carcinogenesis [7;8] and the promotion of chemically-induced skin tumors [9]. In contrast, the Fischer rats that were used in this study have varying susceptibility to diverse tumors that is dependent upon both the inducing agent and tumor site [10][11][12][13]. Given the variations in tumor susceptibility observed among different strains of rodents, use of multiple strains of mice and rats may be more reflective of the genetic variability observed in humans.…”
Section: Assessment Of Bisphenol A-induced Carcinogenicity In Adult Rmentioning
confidence: 99%
“…DMBA 1994]. The potential usefulness of these systems is sug-is a potent mammary gland carcinogen in the rat when gested by results with the rat model that demonstrate administered in a single gavage [Huggins et al, 1961; increased mutant frequencies in the livers of animals Isaacs, 1985;Moore et al, 1988]. We previously used treated with tamoxifen [Davies et al, 1996 and this DMBA treatment regimen to induce 6-thioguanineaflatoxin B 1 [Dycaico et al, 1996], and in splenic lympho-resistant (TG r ) lymphocyte mutants in Sprague-Dawley cytes from rats treated with 7,12-dimethylbenz [a]anthra-rats and found that the profile of hprt mutations was concene (DMBA) [Manjanatha et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] The resistance or susceptibility phenotype is tissue specific and cell autonomous, at least in the contrasting strains COP and WF 19 and is not due to differences in carcinogen metabolism. 20 The susceptibility of the rat mammary gland to chemically induced tumours is highest when the inducing carcinogen agent is administered to young virgin females (45 to 60 day-old), when the mammary epithelium proliferation is characterized by a high proliferation rate. 6 The mammary glands contain a multitude of lactiferous ducts composed of 2 main cell types forming the epithelial and myoepithelial layers.…”
mentioning
confidence: 99%